Agricultural Growth Corridors and the Potential for CGIAR Research - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
This brief is based on a study commissioned by the ISPC in 2015 which highlights the potential risks and opportunities of agricultural corridors and spatial development initiatives and their impact on CGIAR research.